Policy Diffusion, Digitalisation, and Governance Gaps in the Implementation of Indonesia's Golden Visa Programme - Gunawan Ari Nursanto; Sunarto Sunarto; Pandji Sukmana; Gatot Hery Djatmiko (Master's Programs in International Relations, Faculty of Social and Political Science, Jenderal Achmad Yani University (UNJANI)., 2025)
Indonesia’s Golden Visa, launched in 2023 through Minister of Law and Human Rights Regulation No. 22/2023, is promoted as a residence-by-investment scheme to attract foreign capital and talent for post-pandemic recovery and digital transformation. This article uses a qualitative descriptive approach based on documentary analysis of regulations, internal guidance, official statistics, and scholarly literature on Golden Visa programmes, investment migration, and digital immigration governance. It examines how Indonesia’s scheme is designed and how far its monitoring and governance arrangements are specified.The findings show that Indonesia, as a latecomer, selectively borrows design elements from European models longer residence durations, high investment thresholds, and privileged treatment for targeted investors and global talents—while embedding the programme in a digital-by-design architecture with online application and stay-permit services. However, there is a gap between relatively sophisticated ex-ante design and under-specified ex-post monitoring and evaluation. References to investment realisation, supervision, and revocation lack operational detail on risk-based triggers, inter-agency coordination, and data governance. The article argues that Indonesia’s Golden Visa must move beyond investment-promotion rhetoric toward an end-to-end, digitally supported monitoring model and contributes to debates on policy diffusion, investor migration, and digital governance by emphasising institutional capacity and accountability.